Liquid crystalline hyperbranched polyesters with phosphorus functional groups. (May 2021) - Serbezeanu, Diana; Macsim, Ana-Maria; Carja, Ionela-Daniela; Hamciuc, Corneliu; Pislaru, Marius; Vlad-Bubulac, Tăchiţă
Liquid crystalline hyperbranched poly(aryl ester)s (A2 B3 ) were prepared by polycondensation reaction of 2-(6-oxido-6H-dibenz<c, e><1, 2>oxaphosphorin-6-yl)1, 4-naphthalene diol with 1, 3, 5-benzenetricarbonyl trichloride, taken in two different molar ratios. The chemical structure of the newly synthesized hyperbranched polymers was confirmed by FTIR, 1 H NMR, 13 C NMR spectroscopy. The polymers exhibited high thermal stability with initial decomposition temperature above 410–435°C and char yield at 700°C higher than 40%. Combined differential scanning calorimetry, polarized optical microscopy and wide-angle X-ray diffraction measurements were carried out to closely examine their thermal behavior and phase transitions.